2005
DOI: 10.1097/00006982-200507000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Endovascular Surgery for Central Retinal Vein Occlusion

Abstract: Although the authors were on the "learning curve" of experience during this series, REVS appears to promote visual recovery far in excess of what would be expected to occur spontaneously, and IVTA injection greatly improved outcomes. We believe that mastery of REVS techniques and the inclusion of IVTA injection may lead to better visual results and lower complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 12 publications
0
35
0
1
Order By: Relevance
“…This technique works by several different mechanisms: firstly, pars plana vitrectomy with removal of posterior hyaloid provides high oxygen levels to retina, relieves macular traction and contributes to resolution of macular edema ; secondly, direct injection of t-PA causes lyses of trombus by providing high local concentration and thirdly, bolus of t-PA may flush out the trombus with its high flow velocity [21] . Similarly, Bynoe et al [22] revealed favorable results with retinal endovascular surgery.…”
Section: Introductionmentioning
confidence: 83%
“…This technique works by several different mechanisms: firstly, pars plana vitrectomy with removal of posterior hyaloid provides high oxygen levels to retina, relieves macular traction and contributes to resolution of macular edema ; secondly, direct injection of t-PA causes lyses of trombus by providing high local concentration and thirdly, bolus of t-PA may flush out the trombus with its high flow velocity [21] . Similarly, Bynoe et al [22] revealed favorable results with retinal endovascular surgery.…”
Section: Introductionmentioning
confidence: 83%
“…Among a variety of surgical tools in ophthalmic operations, the beveled needle is a widely used surgical instrument for delivering the drug into micro-structural anatomies of the eye such as retinal blood vessels and sub-retinal areas. Many studies have been carried out with significant progress in the needle segmentation through microscopic images [5][6][7][8]. These works achieved satisfactory results using either color-based or geometry-based features.…”
Section: Introductionmentioning
confidence: 99%
“…These vessels have a cross section diameter of 80µm. A promising treatment is the injection of clot-dissolving drugs such as, tissue Plasminogen Activator (tPA) directly into the affected vessel [2]. Wei et al suggested a method using stenting as a surgical solution for Central Retinal Vein Occlusion (CRVO) [3].…”
Section: Introductionmentioning
confidence: 99%